2011
DOI: 10.3133/sir20115055
|View full text |Cite
|
Sign up to set email alerts
|

Geologic framework and hydrogeology of the middle Carson River Basin, Eagle, Dayton, and Churchill Valleys, West-Central Nevada

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit http://store.usgs.gov Any use of trade, product, or firm names is for descriptive purposes only and does not imply endorsement by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Carson Valley is a semiarid agricultural basin with characteristics of the basin and range province of the western United States. Generalized water budget and hydrogeologic conditions (i.e., natural recharge and discharge, river flows, hydrogeologic properties) were developed based on previous studies of the Carson River basin [ Maurer , ; Huntington and Allen , ]. Although many characteristics represented in the test model are derived from Carson River basin studies, the model differs in particular aspects of physiography that were made to simplify particular details not important to this analysis and/or to promote generality.…”
Section: Test Model For Ag‐marmentioning
confidence: 99%
“…Carson Valley is a semiarid agricultural basin with characteristics of the basin and range province of the western United States. Generalized water budget and hydrogeologic conditions (i.e., natural recharge and discharge, river flows, hydrogeologic properties) were developed based on previous studies of the Carson River basin [ Maurer , ; Huntington and Allen , ]. Although many characteristics represented in the test model are derived from Carson River basin studies, the model differs in particular aspects of physiography that were made to simplify particular details not important to this analysis and/or to promote generality.…”
Section: Test Model For Ag‐marmentioning
confidence: 99%
“…The model was designed, through appropriate selection of packages available with MODFLOW-NWT (Niswonger and others, 2011), to help water managers assess the future effects of alternative management decisions made today in response to a growing need for water. The model synthesizes a broad body of information about the MCR that was collected as part of a cooperative study between the USGS and Reclamation that began in 2008, the results of which are reported in Jeton and Maurer (2011) and Maurer (2011). Data from the cooperative studies were compiled and used to develop (1) the hydrogeologic framework; (2) distributions of precipitation, runoff, and infiltration in 12 perennial and ephemeral tributaries along the MCR; (3) key characteristics of the surface-water network, including identification of gaining and losing stretches of the middle Carson River study area; and (4) surface-water flow and groundwater hydraulic head observations (Jeton and Maurer, 2011;Maurer, 2011).…”
Section: Purpose and Scopementioning
confidence: 99%
“…The model synthesizes a broad body of information about the MCR that was collected as part of a cooperative study between the USGS and Reclamation that began in 2008, the results of which are reported in Jeton and Maurer (2011) and Maurer (2011). Data from the cooperative studies were compiled and used to develop (1) the hydrogeologic framework; (2) distributions of precipitation, runoff, and infiltration in 12 perennial and ephemeral tributaries along the MCR; (3) key characteristics of the surface-water network, including identification of gaining and losing stretches of the middle Carson River study area; and (4) surface-water flow and groundwater hydraulic head observations (Jeton and Maurer, 2011;Maurer, 2011). Thus, the MCR modeling study codifies results from multiple studies between the USGS and Reclamation to help guide resource managers with the long-term sustainable management of water resources in the region.…”
Section: Purpose and Scopementioning
confidence: 99%
See 2 more Smart Citations